Daily variability in mood and subjective cognitive function: An experience sampling study in young adults - Melanie A. Butt; Todd C. Handy (PLoS ONE, 2026)
In older adults, greater day-to-day fluctuations in cognitive function appear to be associated with higher rates of cognitive decline, relative to those showing less daily cognitive variability. Such findings suggest that within-person daily deviations from an individual’s typical functioning do not simply represent measurement noise, but rather, vitally inform on cognitive status in older adults. But what about these dynamics in younger adults? Does daily variability in cognition potentially inform on cognitive wellness for those in their neurocognitive prime? Here we addressed this question using an experience sampling method to assess participants’ subjective sense of their cognition and mood three times a day over 14 days in a sample of 215 young, healthy adults. After controlling for four baseline measures of subjective cognition (metacognitive awareness, executive function, propensity for cognitive failures, and memory failures) and four baseline measures of mood (depression, state and trait anxiety, and loneliness), we found that not only did subjectively-assessed cognitive function show significant within-person day-to-day variability across the sample population, but greater person-level cognitive variability across the two-week period predicted lower mean perceived function across the two weeks. While daily cognitive variability also showed a significant correlation with daily measures of both negative and positive mood, notably, some individuals were more resilient to these daily mood impacts on subjective cognition than others. Taken together, our findings suggest that daily variability in subjective cognition and mood may be important predictors for understanding cognitive wellness in younger adult populations.